Experiential Marketing Wisata Taman Kota Surabaya - Citra Anggraini Tresyanto; Bruno Hami (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
The public need big cities nowadays are very complex. No exception to the needs of the people of Surabaya. One of the new needs of urban society is traveled. Traveled synonymous with waste of money. Not at this time, traveled enough to spend time with visiting the city park. Surabaya has a lot of city parks that can be utilized by the community. A total of 27 active city park owned by Surabaya. But unfortunately some of them, can be utilized by the community. Apart from that, the city park form a new lifestyle and needs in the community that traveled in a city park. Travelling in the city park provides an exciting experience. An interesting experience can be formed through a component in experiential marketing, namely sense, feel, think, act and relate that will describe a new experience as a result of a particular stimulus. Through experiential marketing also, the city government can find out what people felt after visiting the city and what is needed by the community. Proved that the city parks are built and design well, according to the needs and expectations of the community. This is clearly evident from the many community activities in the city park on the weekends.